Subpial hemorrhage: A rare and underrecognized site of intracranial hemorrhage in neonates - Anass El M Aary (Radiology Case Reports)
Subpial hemorrhage (SPH) is a rare but significant cause of neonatal seizures and respiratory distress, primarily affecting full-term infants without apparent risk factors. We report the case of a full-term newborn who presented with recurrent episodes of apnea, desaturation, and seizures shortly after birth. MRI revealed an acute hemorrhagic collection in the left temporal region, accompanied by cortical cytotoxic edema. The diagnosis of SPH was established based on characteristic imaging findings. The patient was treated with anticonvulsant therapy and intensive neonatal care, leading to a favorable outcome. Early diagnosis through neuroimaging, particularly MRI, is crucial for proper management, as SPH may be missed on routine ultrasound. Despite its rarity, SPH generally carries a good prognosis with timely intervention, although larger hemorrhages or cases in preterm infants may have a more uncertain prognosis.